Directing spatial attention in mental representations: Interactions between attentional orienting and working-memory load. - Lepsien, J; Griffin, I; Devlin, J; Nobre, A (2005)
Orienting spatial attention to locations in the extrapersonal world has been intensively investigated during the past decades. Recently, it was demonstrated that it is also possible to shift attention to locations within mental representations held in working memory. This is an important issue, since the allocation of our attention is not only guided by external stimuli, but also by their internal representations and the expectations we build upon them. The present experiment used behavioural measures and event-related functional magnetic resonance imaging to investigate whether spatial orienting to mental representations can modulate the search and retrieval of information from working memory, and to identify the neural systems involved, respectively. Participants viewed an array of coloured crosses. Seconds after its disappearance, they were cued to locations in the array with valid or neutral cues. Subsequently, they decided whether a probe stimulus was presented in the array. The behavioural results indicated that orienting of spatial attention within working memory attenuates the well-known effect of decreasing performance when memory load is increased. So "internal" spatial orienting seems to highlight information or facilitate search within working memory, which leads to advantages in retrieval. Imaging enabled the separation of brain areas supporting spatial orienting functions from those sensitive to working-memory load. Orienting of spatial attention to the contents of working memory activated posterior parietal cortex bilaterally, the insula, and lateral and medial frontal cortices.